Impact of rare-earth metal oxide (Eu 2 O 3 ) on the electrochemical properties of a polypyrrole/CuO polymeric composite for supercapacitor applications - Majumder, Mandira; Choudhary, Ram Bilash; Thakur, Anukul. K.; Karbhal, Indrapal (RSC Advances, 2017)
A ternary composite of polypyrrole/copper oxide/europium oxide (PPY/CuO/Eu2O3), synthesized via a facile in situ chemical oxidative polymerization method, exhibits the maximum specific capacitance of 320 F g⁻¹ at the current density of 1 A g⁻¹. Incorporation of the rare-earth metal oxide Eu2O3 in the PPY/CuO matrix can promote charge transportation in the resulting ternary nanocomposite by enhancing the porosity. The interconnected mesoporous networks reduce the internal resistance and the charge transfer resistance (Rct) of the composite electrode material. Moreover, the incorporation of Eu2O3 in the PPY/CuO provides support to the fragile polymer backbone resulting in an excellent cycle stability and a markedly enhanced thermal stability. These together with the exhibition of an excellent coulombic efficiency demonstrates that incorporation of rare earth metal oxide can play a significant role in improving the performance of a polymeric composite opted as an electrode material for high-performance supercapacitor.